2012
DOI: 10.1007/s00894-012-1385-4
|View full text |Cite
|
Sign up to set email alerts
|

Role of wobble base pair geometry for codon degeneracy: purine-type bases at the anticodon wobble position

Abstract: Codon degeneracy is a key feature of the genetic code, explained by Crick (J Mol Biol 19:548-555, 1966) in terms of imprecision of base pairing at the codon third position (the wobble position) of the codon-anticodon duplex. The Crick wobble rules define, but do not explain, which base pairs are allowed/disallowed at the wobble position of this duplex. This work examines whether the H-bonded configurations of solitary RNA base pairs can in themselves help decide which base pairs are allowed at the wobble posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 59 publications
0
6
0
Order By: Relevance
“…In vitro , Q-modified tRNA bound C-ending triplets more stably than U-ending triplets [31] . Structural studies report that Q-tRNA and G-tRNA have similar codon-recognition properties [42] , as might be naively expected because the ribose moiety differentiating Q from G does not involve the codon-recognizing portion of the nucleoside [43] ( Figure 2B ). Drosophila tRNA His injected into Xenopus oocytes translates NAU more than NAC when Q-modified and NAC when unmodified [44] .…”
Section: Resultsmentioning
confidence: 76%
“…In vitro , Q-modified tRNA bound C-ending triplets more stably than U-ending triplets [31] . Structural studies report that Q-tRNA and G-tRNA have similar codon-recognition properties [42] , as might be naively expected because the ribose moiety differentiating Q from G does not involve the codon-recognizing portion of the nucleoside [43] ( Figure 2B ). Drosophila tRNA His injected into Xenopus oocytes translates NAU more than NAC when Q-modified and NAC when unmodified [44] .…”
Section: Resultsmentioning
confidence: 76%
“…Thus, one might expect that queuosine modification does not affect the ability of the tRNA Asp to base-pair with the cognate aspartate codons. However, computational studies on the RNA bases concluded that queuine may have a slightly disfavored base pairing with cytosine as well as uracil [48]. This would suggest a weaker binding of Q than G and possibly a negative effect on codon-anticodon base pairing.…”
Section: Molecular Consequences Of Queuosine Modification and Dnmtmentioning
confidence: 99%
“…Especially the disallowance of guanosine-guanosine (G-G) pairing can involve a hydrogen bond between the N7 hydrogen of one G and the amino group of the other G [48]. This hydrogen bond is not possible with Q, since it lacks the 7-N position.…”
Section: Molecular Consequences Of Queuosine Modification and Dnmtmentioning
confidence: 99%
“…Base pairings between unmodified A34 and N(III) (where N denotes U, C, A, or G at the third position of the codon) are theoretically possible, though they are unstable or nonproductive, and sequencing analyses of tRNA gene sets from various organisms have revealed deductively that unmodified A34 can recognize all four nucleotides at the wobble position of the codon [ 11 , 13 , 14 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Pairings between A34 and R(III) (where R denotes a purine nucleotide) are particularly unstable, and they have been predicted to form only with non-canonical conformations of nucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…The pairing of the ICG anticodon with the CGG codon does not occur because the I34-G(III) pairing likely causes steric hindrance, although it is possible only when it involves unusual tautomerization or geometry of nucleotides under specific conditions [ 13 , 24 , 27 , 28 , 29 ]. Thus, tRNA Arg (CCG) should be required for decoding CGG codons ( Figure 2 ), and both tRNA Arg (ICG) and tRNA Arg (CCG) have been shown indispensable for the viability of E. coli [ 33 ].…”
Section: Introductionmentioning
confidence: 99%